On existence and uniqueness of generalized solutions for a mixed-type differential equation. - Elzaki, Tarig M.; Kilicman, Adem; Eltayeb, Hassan (Canadian Center of Science and Education, 2010)
In this paper, we study a boundary value problem for a mixed–type differential equation. The existence and uniqueness of generalized solution is proved. The proof is based on an energy inequality and the density of the range of the operator generated by this problem.